2015
DOI: 10.1103/physrevb.91.115107
|View full text |Cite
|
Sign up to set email alerts
|

Localization length index and subleading corrections in a Chalker-Coddington model: A numerical study

Abstract: We calculated numerically the localization length index ν for the Chalker-Coddington model of the plateau-plateau transitions in the quantum Hall effect. By taking into account finite size effects we have obtained ν = 2.593 ± 0.0297. The calculations were carried out by two different programs that produced close results, each one within the error bars of the other. We also checked the possibility of logarithmic corrections to finite size effects and found, that they come with much larger error bars for ν. PACS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 25 publications
3
26
1
Order By: Relevance
“…They include the localization length exponent ν IQH ¼ 2.56-2.62 and the leading irrelevant exponent y ≃ 0.4 (with large error bars). At criticality, y describes the approach of the dimensionless quasi-1D Lyapunov exponent Γ to its limiting value at infinite system size Γ IQH 0 ¼ 0.77-0.82 [5][6][7]9,[11][12][13]16]. A similar exponent y was found for the average conductance ḡ of a square sample with limiting value ḡIQH ¼ 0.58-0.62 [19,20].…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…They include the localization length exponent ν IQH ¼ 2.56-2.62 and the leading irrelevant exponent y ≃ 0.4 (with large error bars). At criticality, y describes the approach of the dimensionless quasi-1D Lyapunov exponent Γ to its limiting value at infinite system size Γ IQH 0 ¼ 0.77-0.82 [5][6][7]9,[11][12][13]16]. A similar exponent y was found for the average conductance ḡ of a square sample with limiting value ḡIQH ¼ 0.58-0.62 [19,20].…”
mentioning
confidence: 58%
“…The integer quantum Hall transition (IQHT) at E ¼ E c is the most studied Anderson transition [2] because of its conceptual simplicity, low dimensionality, and experimental relevance. However, critical properties at the IQHT are notoriously difficult to compute analytically; they are mostly known from numerical studies which employed the Chalker-Coddington (CC) network model [3][4][5][6][7][8][9][10][11][12][13], microscopic continuous [14,15], lattice [10,[14][15][16][17], and Floquet Hamiltonians [18]. In recent works, the critical properties agree among models, indicating universality of the IQHT.…”
mentioning
confidence: 99%
“…40 The regular geometry of the CC model allows one to apply numerical transfer matrix techniques. 41,42 Recent implementations of this [43][44][45][46][47][48] and other methods 49,50 agree on the value ν in the range 2.56-2.62, certainly different from ν exp . The discrepancy points to the importance of the long-range electron-electron interaction, which certainly affects the scaling near the integer QH transition [51][52][53][54][55][56][57][58] and is relevant for the interpretation of experiments.…”
Section: -30mentioning
confidence: 80%
“…48 Since t and r appear in the denominators of the matrix elements of transfer matrices, making them zero is a singular procedure, related to the disappearance of two horizontal channels upon opening a node in the vertical direction. To overcome this difficulty, for every open node we take either t or r to be equal to ε 1.…”
Section: Construction and Simulation Of Random Networkmentioning
confidence: 99%
“…In light of the notorious difficulty with analytical approaches to the IQHT, this relation is at the heart of a long history of numerical finite-size scaling studies, mostly employing the Chalker-Coddington (CC) network model. [4][5][6][7][8][9][10][11][12][13][14] These works report ν = 2.56-2.62 but the leading irrelevant exponent y 0.4 is suprisingly small and comes with large error bars. While the above results were reproduced in a recent lattice model simulation, 15 Zhu et al reported a slightly different but incompatible value ν = 2.46-2.50 obtained from scaling the total number of conducting states in both lattice and continuum models projected to the lowest Landau level.…”
Section: Introductionmentioning
confidence: 99%